Network Meta-Analysis of Metabolic Effects of Olive-Oil in Humans Shows the Importance of Olive Oil Consumption With Moderate Polyphenol Levels as Part of the Mediterranean Diet - Tsartsou, Evangelia; Proutsos, Nikolaos; Castanas, Elias; Kampa, Marilena (Frontiers in Nutrition, 2019)
The beneficial role of olive oil consumption is nowadays widely recognized. However, it is not clear whether its health effects are due to the presence of monounsaturated lipids and/or to the antioxidant fraction of microconstituents present in olive oil. The aim of the present study was to analyze the exact role of olive oil in the modification of metabolic factors (glucose and circulating lipids) and explore the role of its antioxidant polyphenols. In the present work, we have performed a network meta-analysis of 30 human intervention studies, considering direct and indirect interactions and impact of each constituent. Interestingly, we show that the impact of olive oil on glucose, triglycerides, and LDL-cholesterol is mediated through an adherence to the Mediterranean diet, with the only notable effect of olive oil polyphenols being the increase of HDL-cholesterol, and the amelioration of the antioxidant and inflammatory status of the subjects. Additionally, we report for the first time that lower antioxidant polyphenol levels may be sufficient for the beneficial effects of olive oil, while we show that the lipid fraction of olive oil may be responsible for some of its beneficial actions. In all parameters examined the beneficial effect of olive oil was more pronounced in subjects with an established metabolic syndrome or other chronic conditions/diseases. In conclusion, all these findings provide new knowledge that could lead to re-establishment of the role of olive oil in human nutrition.